Pendampingan Penyusunan Pedoman Survei Kepuasan Masyarakat di Lingkungan Bawaslu - Fatkhuri; Shanti Darmastuti; Afrimadona Afrimadona (CV. Multi Kreasi Media, 2022)
Abstract- This service was done to help the Election Supervisory Agency of Indonesia (Bawaslu RI) in compiling the Manual Book of Community Satisfaction Survey. The Community Satisfaction Survey is necessary effort to improve the services provided. The preparation of this manual book is very urgent because the agency has the responsibility to accelerate bureaucratic reform as mandated by Presidential Regulation number 10 regarding of the Grand Design of Bureaucratic Reform 2010-2025. Based on an analysis, the results of the assessment of bureaucratic reform including public services within the agency have not obtained maximum results despite an increasing trend in recent years. On the other hand, the Election Supervisory Agency of Indonesia doesn't have a technical guide yet to measure the performance of services that have been carried out. The results of community service focus on the preparation of the Community Satisfaction Survey Book. This book is very helpful for the Election Supervisory Agency of Indonesia to improve the performance of public services through the implementation of the Community Satisfaction Survey which will be carried out within the agency's environment at all levels. The results of this service activity can of course be a reference for all election supervisory organizers throughout Indonesia, especially in relation to how to carry out the duties and functions of public services for the community in a measurable and sustainable manner.